2020
DOI: 10.1039/d0se01110j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of jet fuel range high-density dicycloalkanes with methyl benzaldehyde and acetone

Abstract: In this work, jet fuel range high-density dicycloalkanes were manufactured from methyl benzaldehyde and acetone, two platform compounds which may be obtained from lignocellulose. Protonated titanate nanotube (PTNT), a cheap...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Recent advances in nanoscience and nanotechnology have paved the way for more operational, “green,” and long-lasting nanostructured catalytic systems. Due to their unique physicochemical properties, for instance, a high surface-to-volume ratio, strong dispersibility, and increased accessibility of surface hydroxyl groups, Lewis acid sites (LAS) and Bronsted acid sites (BAS), 1D HTNT has been established as attractive catalysts and supports [ 8 , 11 13 ]. Given that nanomaterials are a type of material whose dimensions are described by the nanometer scale (typically ranging from 1 to 100 nm) in the field of nanoscience and nanotechnology [ 28 – 31 ], the term “nanostructure” is commonly used to designate the geometrical structure of nanomaterials.…”
Section: One-dimensional (1d) Nanostructured Titanate Materials—the Efficient Solid Acid Catalyst Of High Value!mentioning
confidence: 99%
See 4 more Smart Citations
“…Recent advances in nanoscience and nanotechnology have paved the way for more operational, “green,” and long-lasting nanostructured catalytic systems. Due to their unique physicochemical properties, for instance, a high surface-to-volume ratio, strong dispersibility, and increased accessibility of surface hydroxyl groups, Lewis acid sites (LAS) and Bronsted acid sites (BAS), 1D HTNT has been established as attractive catalysts and supports [ 8 , 11 13 ]. Given that nanomaterials are a type of material whose dimensions are described by the nanometer scale (typically ranging from 1 to 100 nm) in the field of nanoscience and nanotechnology [ 28 – 31 ], the term “nanostructure” is commonly used to designate the geometrical structure of nanomaterials.…”
Section: One-dimensional (1d) Nanostructured Titanate Materials—the Efficient Solid Acid Catalyst Of High Value!mentioning
confidence: 99%
“…Herein, we report a series of published works of a new kind of efficient sodium/protonated titanate nanotubes hydrothermally obtained via nanotechnology applications. The current method holds a lot of promise for the future development of new families of cost-effective and reliable solid catalysts on eco-friendly precursors, scalable and sustainable protocols [ 1 , 8 , 9 , 12 , 13 ]. The benefits of solid acid catalysts as heterogeneous over homogeneous in chemical industrial transformation processes have been previously reported Hideshi Hattori et al[ 41 ]…”
Section: One-dimensional (1d) Nanostructured Titanate Materials—the Efficient Solid Acid Catalyst Of High Value!mentioning
confidence: 99%
See 3 more Smart Citations